Co-regulating the Indonesian Digital Economy - Ira Aprilianti; Siti Alifah Dina (Center for Indonesian Policy Studies (CIPS), 2021)
Indonesia's digital economy experienced the fastest growth among Southeast Asian countries in 2019. The Covid-19 pandemic has accelerated this trend. In doing so, it has also expanded economic opportunities for millions of Indonesians that could support economic recovery and even economic growth for the country. However, an appropriate regulatory approach is urgently needed to accommodate emerging business models and innovations in the digital space. To promote an enabling digital economy that is safe, trusted, and inclusive, policy solutions are needed in four key areas: consumer protection, data privacy, cybersecurity, and e-payments. This policy paper outlines how co-regulation could be the most appropriate approach amid Indonesia's rapidly changing digital economy landscape.
Keywords: 330; digital economy; digital indonesia; coregulation; digital economy policy; public private dialogue; cyber security; e-payment; data privacy; siti alifah dina; ira aprilianti; regulatory sandbox; OJK; CIPE; co-regulating